Mengeksplorasi Pro-Kontra Pemanfaatan Teknologi AI Bagi Mahasiswa Pgmi Unzah Sebagai Calon Guru Di Tingkat Dasar - Taufik, Mohammad; Zainuddin, Zainuddin; Mufidah, Nani Zahrotul (STKIP Singkawang, 2025)
This article discusses the role of artificial intelligence (AI) technology in preparing students of the Elementary Madrasah Teacher Education Study Program (PGMI) at Zainul Hasan University (UNZAH) as prospective teachers at the elementary education level. This study uses a qualitative approach to explore the pros and cons of the use of AI technology in education. The results of the study indicate that AI technology has the potential to increase learning effectiveness, facilitate learning personalization, and provide richer educational resources. However, on the other hand, there are challenges that must be faced, such as dependence on technology, data privacy issues, and the potential for reducing human interaction in the teaching and learning process. By understanding these two perspectives, it is hoped that this study can provide insight into the development of the UNZAH PGMI curriculum and the integration of AI technology in the educational process at the elementary level.